Medicine and healing in the ancient Mediterranean world : including the proceedings of the international conference with the same title, organised in the framework of the Research Project INTERREG IIIA : Greece/Cyprus 2000/2006, Joint Educational and Research Programmes in the History and Archaeology of Medicine, Palaeopathology, and Palaeoradiation, and the 1st International CAPP Symposium "New Approaches to Archaeological Human Remains in Cyprus" - Michaēlidēs, Dēmētrēs (Oxbow Books, 2014)
There are many recoverable aspects and indications concerning medicine and healing in the ancient past -- from the archaeological evidence of skeletal remains, grave-goods comprising medical and/or surgical equipment and visual representations in tombs and other monuments thorough to epigraphic and literary sources. The 42 papers presented here cover many aspects medicine in the Mediterranean world during Antiquity and early Byzantine times, bringing together both internationally established specialists on the history of medicine and researchers in the early stages of their career. The contributions are grouped under a series of headings: medicine and archaeology; media (online access to electronic corpus); the Aegean; medical authors/schools of medicine; surgery; medicaments and cures; skeletal remains; new research in Cyprus; Asklepios and incubation; and Byzantine, Arab and medieval sources. These subject areas are addressed through a combination of wide ranging archaeological and osteological data and the examination and interpretation of philosophical, literary and historiographical texts to provide a comprehensive suite of studies into early practices in this fundamental field of human experience.